2009
DOI: 10.1104/pp.109.141267
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Scale Metabolic Model of Arabidopsis and Some of Its Properties    

Abstract: We describe the construction and analysis of a genome-scale metabolic model of Arabidopsis (Arabidopsis thaliana) primarily derived from the annotations in the Aracyc database. We used techniques based on linear programming to demonstrate the following: (1) that the model is capable of producing biomass components (amino acids, nucleotides, lipid, starch, and cellulose) in the proportions observed experimentally in a heterotrophic suspension culture; (2) that approximately only 15% of the available reactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
288
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(300 citation statements)
references
References 48 publications
(52 reference statements)
6
288
1
1
Order By: Relevance
“…For example, in a recent computational study, Poolman et al (2009) reported a nonzero Rubisco oxygenase reaction as a result of a constraint-optimization problem in heterotrophic Arabidopsis cells. While the scenario discussed therein is probably unlikely to occur in vivo, as also acknowledged by the authors (Poolman et al, 2009;Stitt et al, 2010), the prediction of flux through previously unrecognized reactions as a result of network optimization is not unusual (Schwender et al, 2004). In this sense, a thorough network reconstruction allows researchers to evaluate the inevitable functional consequences, given the current annotation and knowledge of enzymatic interconversions, and thus opens the possibility of specifically designing experiments to distinguish between alternative hypotheses.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent computational study, Poolman et al (2009) reported a nonzero Rubisco oxygenase reaction as a result of a constraint-optimization problem in heterotrophic Arabidopsis cells. While the scenario discussed therein is probably unlikely to occur in vivo, as also acknowledged by the authors (Poolman et al, 2009;Stitt et al, 2010), the prediction of flux through previously unrecognized reactions as a result of network optimization is not unusual (Schwender et al, 2004). In this sense, a thorough network reconstruction allows researchers to evaluate the inevitable functional consequences, given the current annotation and knowledge of enzymatic interconversions, and thus opens the possibility of specifically designing experiments to distinguish between alternative hypotheses.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Specifically, FBA allows the prediction of optimal steady-state fluxes that maximize a given objective function, usually the synthesis of biomass or biomass precursors required for growth. Although certainly not without pitfalls, the predictions of FBA have proven to reasonably reflect the modes of cellular operation, with manifold applications ranging from microorganisms to algae and plant metabolism (Varma and Palsson, 1994;Shastri and Morgan 2005;Boyle andMorgan, 2009, Feist et al, 2009;Grafahrend-Belau et al, 2009;Oberhardt et al, 2009;Poolman et al, 2009).…”
mentioning
confidence: 99%
“…Moreover, these models can contextualize multiple omics data through several integrative analyses, as such providing unique biological insights at the systems level (Hyduke et al, 2013). Several constraints-based models have been developed at the genome scale for a wide range of microbes and mammals (Kim et al, 2012b), including humans (Duarte et al, 2007), and a few plants, such as Arabidopsis (Poolman et al, 2009;Saha et al, 2011;MintzOron et al, 2012;Chung et al, 2013), maize (Saha et al, 2011;Simons et al, 2014), and rice (Poolman et al, 2013). Among these, the human genome-scale metabolic model (GEM) has been integrated with transcriptome and proteome data to characterize the transcriptional regulatory mechanisms and metabolic phenotypes of various diseases, which could not be deciphered from either of them alone (Zelezniak et al, 2010;Hu et al, 2013;Mardinoglu et al, 2014).…”
mentioning
confidence: 99%
“…In this regard, metabolic network models for several plants, such as Arabidopsis (Arabidopsis thaliana; Poolman et al, 2009;de Oliveira Dal'Molin et al, 2010a;Saha et al, 2011;Chung et al, 2012;Mintz-Oron et al, 2012), barley (Hordeum vulgare;Grafahrend-Belau et al, 2009), rapeseed (Brassica napus;Hay and Schwender, 2011;Pilalis et al, 2011), maize (Zea mays; Saha et al, 2011), and a general C 4 plant model (de Oliveira Dal'Molin et al, 2010b) have already been developed, and some of them are even in genome scale. Nevertheless, to the best of our knowledge, the metabolic model of rice is not available to date.…”
mentioning
confidence: 99%